Methylenecyclopropylglycine and hypoglycin A intoxication in three Pére David's Deers (Elaphurus davidianus) with atypical myopathy. Issue 3 (13th December 2020) - Bochnia, Mandy; Ziemssen, Eva; Sander, Johannes; Stief, Birgit; Zeyner, Annette
Abstract: Background: Hypoglycin A (HGA) and methylenecyclopropylglycine (MCPrG) from seeds/seedlings of Sycamore maple (SM, Acer pseudoplatanus ) causes atypical myopathy (AM) in horses. AM was not known to occur in wild ruminants until several fatalities in milus ( Elaphurus davidianus ) following the ingestion of HGA in SM seeds. However, a role for MCPrG has not previously been evaluated. Objectives: To test the hypothesis that MCPrG is also a major factor in AM in milus, three milus (M1, M2, M3) from the Zoo Dresden (aged 7–11 years, 2 females and 1 male, in good nutritional condition) that developed AM were studied. Methods: Serum, urine and methanol extracts from the liver, kidney, rumen digesta and faeces were analysed by ultrahigh‐performance liquid chromatography‐tandem mass spectrometry for HGA, MCPrG and for conjugates of carnitine (C) and glycine (G): Methylenecyclopropylacetyl (MCPA)‐G, MCPA‐C, Methylenecyclopropylformyl (MCPF)‐G, MCPF‐C, butyryl‐C and isobutyryl‐C. Results: HGA in serum was high (M2 480 nmol/L; M3 460 nmol/L), but MCPrG was not. HGA and MCPrG were found in rumen and faeces extracts, and MCPrG was also identified in the liver. Metabolites of HGA and MCPrG were high in serum, urine and liver, but not in the rumen or faeces. Conclusions: This study shows that MCPrG is involved in the pathophysiology of AM in milus. The metabolism of MCPrG is considered to be faster because, after ingestion, the specific metabolites appear highly concentrated in the serum. The high toxin concentration in the liver suggests that a possible transfer into products for human consumption may pose a risk. Abstract : In humans and equines, the intoxication with Methylenecyclopropylglycine (MCPrG) and Hypoglycin A (HGA) from Sapindaceae fruits or seeds is well‐known with a high fatality rate, whereas in horses the common ingestion of both toxins was firstly described in 2019. This study shows for the first time, that also in ruminants both toxins present a major hazard. A possible transfer to the food chain following the consumption of products from affected ruminants by humans should be taken into consideration.